Efektivitas Model Pembelajaran Problem Based Learning Dan Project Based Learning Ditinjau Dari Keterampilan Berpikir Kritis Pada Pembelajaran Tematik Siswa Kelas V SD: The Effectiveness Of The Problem Based Learning And Project Based Learning Models Is Seen From Critical Thinking Skills In Thematic Learning Of Grade V Elementary School Students - Muhammad Abdul Aziz; Suhandi Astuti (Tunas: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This assessment activity was carried out to determine the effectiveness of problem-based teaching models and project-based teaching to foster critical character in integrated teaching of grade V elementary school students. The type of research used as a reference in this assessment activity is Quasi-Experimental research with a Nonequivalent Control Group design. A total of 100 grade V students in the Baratha Cluster in Susukan District were used as a population in this assessment activity, but only 71 students from SDN Koripan 04, SDN Koripan 01, and SDN Koripan 02 were used as research samples. The results of data processing using the T-test show a Sig. (2-tailed) value of 0.000 < 0.05 then  rejected and accepted, meaning that there is a difference in significance values from the two models, where in the problem-based teaching group there was an average increase of 21,167 while in the project-based teaching group of 5,429. By referring to these data, it can be seen that the problem-based teaching model has a greater level of effectiveness than the project-based teaching model in improving critical thinking skills in thematic learning of grade V elementary school students.